Land Sales and Rental Markets in Transition: Evidence from Rural Vietnam - Deininger, Klaus (2012)
Impact and desirability of land transfers in post-socialist-transition economies have been subject of considerable debate. We use data from Vietnam to identify factors conducive to the development of land markets and to assess potentially differential impacts of rental and sales. Results show that both rental and sales transfer land to more productive producers but that rental is more important for the poor to access land that becomes available as the non-farm economy develops. The fact that secure land rights significantly increase supply of land to the rental market suggests that government has a key role in facilitating emergence and functioning of efficiency-enhancing land markets.